Hidrólise e fermentação do bagaço de cana-de-açúcar em escala de bancada para produção de etanol 2G - Carli, Chanel Moacyr de (2011)
The objective of this work was to evaluate the hydrolysis and alcoholic fermentation stages of the sugar cane bagasse (SCB) for second generation ethanol production (2G). Hydrolysis experiments were carried out employing 8%, 10%, 15% and 20% (m/v) solid loads. Samples of in natura SCB and steam exploded SCB were submitted to different pretreatment sequences: water + 4.0% NaOH solution; 1.0% H2SO4 solution + 4.0% NaOH 4%; 1.0% H2SO4 solution + 7.0% NaOH solution; 7.0% NaOH solution; aqueous ammonia; water. Pretreated bagasse was characterized (chemical analysis and SEM) and the mass yield of each sequence was evaluated. This material was employed in hydrolysis experiments using different enzyme loads (33, 65 and 98 FPU/g-cellulose). Three different configurations were evaluated: SHF Separated Saccharification and Fermentation, SSF Simultaneous Hydrolysis and Fermentation, and FB Fed-Batch. In these experiments it was employed Accelerase 1500 enzymatic extract (Genencor). Concerning cellulose loss, SCB pretreated with water and 4.0% of NaOH solution presented the best result (23.9%). For this case, the hemicellulose and ligning removal was 73.7% and 79.1%, respectively. For the others pretreatment sequences the hemicellulose and lignin removal range from 72.3 to 92.2%. For lignin removal the values range from 60.0 and 88.9%. Experiments employing high solid load (20%) resulting in a more concentrated hydrolyzed (ca. 110 g/L). In this experiment it was achieved 64% of cellulose to glucose conversion in 34 hour. The fermentation experiments were carried out employing Saccharomyces cerevisiae yeast (lyophilized commercial). The yield ranges from 75 to 94%. Experiment conducted in the SSF configuration achieved 86.5% of cellulose to ethanol conversion in 14 hours. Experiment carried out in SHF configuration achieved 63.2% of cellulose to ethanol conversion in 37 hours. Experiments carried out in FB configuration reached larger amount of glucose with the same enzyme load employed in batch experiment and at the same time.